Regional collective learning processes, innovation and growth of high technology SMEs: The case of the Cambridge region - David Keeble; Clive Lawson; Barry Moore; Frank Wilkinson (European Regional Science Association (ERSA), 1998)
Recent theoretical research on the technological development of dynamic European regions has drawn attention to the supposedly key role of "untraded interdependencies" between local firms and other organisations (Storper, 1995), involving informal inter-firm networking (Yeung, 1994) and processes of "collective learning" (Camagni, 1991, Lorenz, 1992). These processes, which involve exchange and development of technological expertise, are seen as being based on relationships of trust and reciprocity, while the networks and processes themselves are viewed as influential in the recent evolution of dynamic regional clusters of innovative small and medium sized enterprises. The paper will attempt to assess the extent, importance and nature of collective learning processes in the specific caseof technology-intensive firms in the Cambridge region recenty descried as the "nearest thing in Europe to Silicon Valley" (Martin 1996). Based on an original interview survey of technology-based enterprises, the paper will asses the role of technology firm spin-off and acquistion, inter-firm research and technology collaboration, and scientific and professional labour market recruitment, in the development of local technological competencies and collective learning capabilities. Alltention will also be paid to the role of key local instiutions and supporting business services in this regard. The paper will conclude by condsidering implications for policy.
Keywords: 330